Beyond the Digital Transformation in Omnichannel Transitions: A Scoping Review - Joanna Radomska; Monika Hajdas; Przemysław Wołczek; Arkadiusz Kawa (European Management Studies)
Purpose: We aim to grasp the various facets of shifts towards omnichannel and identify the gaps uncovered by extant scholarship Design/methodology/approach: The research approach is based on a scoping review to investigate the scope of literature on omnichannel transition. Promising avenues for future research were outlined based on the qualitative analysis of extant research. Findings: Based on the scoping review, we identified and proposed further avenues of research. The first avenue explored what makes the transition from single channel to omnichannel a gradual process or an immediate shift rooted in managerial cognition. The second avenue was exploring the transformation process towards omnichannel from the perspective of a strategy-as-practice lens. Research limitations/implications: The research is based on secondary sources. Further research and empirical studies are needed to confirm our findings. Originality/value: We identified the need to address omnichannel transition and transformation separately in further research. We shed some light on these two areas by proposing the cognition perspective and strategy-as-practice theory as theoretical frameworks.